Potential Roles of IT Tools in Health Media Literacy: Analyzing the Views of Digital Media Management Experts - Amir Estakhrian Haghighi; Gholam Oskrochi; Rogheyeh Eskrootchi; Ali Farhangi (Shiraz University of Medical Sciences, 2017)
Background: In the present era, Digital Media Content has played an effective role in the formation of socio-economic and social behaviors. The aim of this research was to investigate the views of media experts in different levels of this filed on factors that affect user-media relationship in the following domains: non-verbal communication, interaction with media audience, effect of media on various domains, attitudes of the audience toward electronic media, and audience's priorities- economic aspects in Iran.Methods: A questionnaire was designed and validated by a pilot study and distributed to a sample of 40 experts and users of digital media on July, 2017. The collected data was analyzed using SPSS Version 22; the significance level was set to 5% in hypotheses testing.Results: The results show that the participants generally agreed on all statements regarding the study domains. However, the level of agreement to all domains was different among different groups of the respondents (mean=14.03 among media strategists as the lowest and mean=35.13 among media managers as the highest levels of agreement, P<0.001) and the domains of the study (mean=28.50 for the higher impact of traditional media and mean=22.50 for the effect of communication technology on increase of interaction between media and audience). Conclusion: The highest rate of agreement was reported for the domain "Traditional media have a higher impact on their audience than the new media, suggesting the importance of traditional media in public knowledge and behavior. However, there was significant difference in the experts' opinions regarding each domain.